Differential methylation status of IGF2‐H19 locus does not affect the fertility of crossbred bulls but some of the CTCF binding sites could be potentially important. Issue 4 (18th February 2014) - Jena, Subas C.; Kumar, Sandeep; Rajput, Sandeep; Roy, Bhaskar; Verma, Arpana; Kumaresan, Arumugam; Mohanty, Tushar K.; De, Sachinandan; Kumar, Rakesh; Datta, Tirtha K.
SUMMARY Associations between abnormal methylation of spermatozoan DNA with male infertility have been sought in recent years to identify a molecular explanation of differential spermatozoan function. The present work was undertaken to investigate the methylation profile of differentially methylated regions (DMRs) in the IGF2‐H19 locus of Bos taurus X Bos indicus crossbred bull spermatozoa. Bulls having more than at least 100 insemination records over a period of 12 years were classified into two groups of five bulls each belonging to low‐ and high‐fertility groups. The IGF2 and H19 DMR sequences in B. indicus cattle were observed to be in absolute homology with B. taurus cattle. The DNA of crossbred bull spermatozoa was isolated, bisulfite treated, and amplified for specific DMR regions using methylation‐change‐specific primers. The overall degree of methylation at IGF2‐H19 DMRs was not found to be significantly different among two groups of bulls. The sixth CTCF binding site (CCCTC) identified in H19 DMR, however, had a significant methylation difference between the high‐ and low‐fertility bulls. It was concluded that alteration of the methylation levels at IGF2‐H19 DMRs might not be responsible for the fertility difference of crossbred bulls, although the role played by the specific CTCF binding sites at this locus, which could influence IGF2 expression during spermatogenesis and early embryonic development, deserves further attention. Mol. Reprod. Dev. 81: 350–362, 2014. © 2014 Wiley Periodicals, Inc.